2006
DOI: 10.1111/j.1365-2141.2006.06248.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SOCS3 is associated with decreased survival in a cohort of patients with de novo follicular lymphoma

Abstract: SummaryThe prognostic significance of SOCS3 protein expression was determined in de novo follicular lymphomas (FL) with t(14;18) and bcl-2 overexpression. Presentation lymph nodes from 82 FL patients for whom clinical information was available were immunohistochemically segregated into SOCS3-positive (n ¼ 42) or -negative (n ¼ 40) cohorts, and overall survival (OS) was analysed. SOCS3-positive FL patients had a median OS of 10 years compared with 22 years in SOCS3-negative patients (P ¼ 0AE001, log rank test).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Methylation silencing of SOCS3 is one of the most important mechanisms of constitutive activation of JAK-STAT pathway in cancer pathogenesis. It has been identified that the methylation of SOCS3 promoter may be involved in the pathogenesis of glioblastoma multiforme (GBM) (Martini et al 2008), follicular lymphoma (Krishnadasan et al 2006), neck and head squamous cell carcinoma (Weber et al 2005), cholangiocarcinoma (Isomoto et al 2007), malignant melanoma (Tokita et al 2007) and hepatocellular carcinoma (Yang et al 2008). SOCS3 itself may function as an important tumor suppressor gene and may be involved in the resistance of these neoplasms to conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation silencing of SOCS3 is one of the most important mechanisms of constitutive activation of JAK-STAT pathway in cancer pathogenesis. It has been identified that the methylation of SOCS3 promoter may be involved in the pathogenesis of glioblastoma multiforme (GBM) (Martini et al 2008), follicular lymphoma (Krishnadasan et al 2006), neck and head squamous cell carcinoma (Weber et al 2005), cholangiocarcinoma (Isomoto et al 2007), malignant melanoma (Tokita et al 2007) and hepatocellular carcinoma (Yang et al 2008). SOCS3 itself may function as an important tumor suppressor gene and may be involved in the resistance of these neoplasms to conventional treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This is strengthened by the inverse correlation between SOCS-3 and FasL expression within PCs, the latter being a mechanism adopted by CLL cells to avoid immunosurveillance [26]. In support of this role, SOCS-3 overexpression reportedly diminishes proliferation of classical Hodgkin lymphoma cell lines [40], whereas its loss has been postulated to predispose for the emergence of a more aggressive disease [39, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…SOCS family members have mechanisms that inhibit JAK/STAT signaling 23, 24. SOCS3 is generally recognized as a tumor suppressor reflecting its inhibition of STAT3 tumorigenesis; however, follicular lymphomas have been reported to show more aggressive behaviors when expressing SOCS3 25. Some studies have also revealed that SOCS3 contributes to cell proliferation in some conditions by suppressing STAT families 26–28…”
Section: Discussionmentioning
confidence: 99%